IMPLEMENTASI APLIKASI E-OFFICE PADA KESEKRETARIATAN BADAN PERENCANAAN PEMBANGUNAN DAERAH PROVINSI KALIMANTAN TIMUR - Suri Handayani (ADMINISTRASI PUBLIK, 2018)
Suri Handayani NPM: 14.11.1001.3509.144, Public Administration Science Program, State Administration Department, Faculty of Social and Political Sciences, "the implementation of e-office application on the secretariat of East Kalimantan Provincial Development Planning Board". Under the guidance of Dr. Marjoni Rachman, M.Si and Dr. H. Mugni Baharuddin, M. Hum.This research is based on the public response to the Organization of Regional Devices (OPD) in supporting the public information disclosure is still very underused or even not known at all either due to lack of information and socialization and the community itself who do not know or do not understand the use and utilization of e- office.The purpose of this study explains how the implementation of e-office applications on the secretariat of the Regional Development Planning Board of East Kalimantan Province in particular in terms of effectiveness. Type of research or explanation used is descriptive research in which using interview techniques, observation, documentation and questionnaires. In this study, which is described is the implementation of e-office applications on the secretariat of East Kalimantan Provincial Development Planning Board.From the results of the research based on the results of the recapitulation of the answers of 15 respondents who have been processed by the researchers, the total score of the overall data collection results is 728 included in the category of interval "quite effective and very effective", but more closely effective. And based on the average respondent answers for all items statement about the effectiveness of employees in implementing e-office that is = (728: 900) x 100% = 81% of the expected 100%.